Glucose modulates food‐related salience coding of midbrain neurons in humans. Issue 12 (13th July 2016) - Ulrich, Martin; Endres, Felix; Kölle, Markus; Adolph, Oliver; Widenhorn‐Müller, Katharina; Grön, Georg
Abstract: Although early rat studies demonstrated that administration of glucose diminishes dopaminergic midbrain activity, evidence in humans has been lacking so far. In the present functional magnetic resonance imaging study, glucose was intravenously infused in healthy human male participants while seeing images depicting low‐caloric food (LC), high‐caloric food (HC), and non‐food (NF) during a food/NF discrimination task. Analysis of brain activation focused on the ventral tegmental area (VTA) as the origin of the mesolimbic system involved in salience coding. Under unmodulated fasting baseline conditions, VTA activation was greater during HC compared with LC food cues. Subsequent to infusion of glucose, this difference in VTA activation as a function of caloric load leveled off and even reversed. In a control group not receiving glucose, VTA activation during HC relative to LC cues remained stable throughout the course of the experiment. Similar treatment‐specific patterns of brain activation were observed for the hypothalamus. The present findings show for the first time in humans that glucose infusion modulates salience coding mediated by the VTA. Hum Brain Mapp 37:4376–4384, 2016 . ©2016 Wiley Periodicals, Inc.